The role of 11beta-hydroxysteroid dehydrogenase 1 in adipogenesis in thyroid-associated ophthalmopathy. - Tomlinson, J; Durrani, O; Bujalska, I; Gathercole, L; Tomlins, P; Reuser, T; Rose, G; Curnow, S; Stewart, P; Walker, E; Rauz, S (2010)
CONTEXT: Thyroid-associated ophthalmopathy (TAO) is a sight-threatening autoimmune disease in which de novo adipogenesis has been identified as a fundamental pathogenic mechanism. 11beta-Hydroxysteroid dehydrogenase 1 (11beta-HSD1) increases cortisol bioavailability and is pivotal in mediating glucocorticoid responses in adipose tissue and inflammation. OBJECTIVE: In this study we characterize 11beta-HSD1 as a determinant of the adipogenic and inflammatory pathways in TAO orbital fat (OF) compared with normal OF. PATIENTS AND METHODS: OF was harvested from 46 TAO and 44 control patients undergoing orbital surgery. Samples were examined by a combination of immunohistochemistry, real-time RT-PCR, primary cell culture, specific enzyme assays, colorimetric proliferation assays, and bead-based ELISA. RESULTS: Glucocorticoid (glucocorticoid receptor-alpha,11beta-HSD1, hexose-6-phosphate dehydrogenase) and inflammatory cytokines (IL-1beta, IL-1 receptor, IL-6, TNF-alpha, TNF-alpha inductible protein, TGF-beta2) target genes together with markers of late adipocyte differentiation (fatty-acid-binding-protein-4, glycerol-6-phosphate-dehydrogenase) were highly expressed in TAO whole OF (P < 0.05) compared with controls. Primary cultures of TAO OF stromal cells demonstrated greater 11beta-HSD1 oxoreductase activity (P < 0.05), which was regulated by cytokines, most notably TNF-alpha (P < 0.01), compared with controls. Activity increased across differentiation, and this was most marked in TAO cells (P < 0.01). Similarly, stromal cell proliferation was limited by incubation with cortisol in TAO cells only. Furthermore, cortisone decreased IL-6 (P < 0.005), IL-8 (P < 0.05), and macrophage chemoattractant protein-1 (P < 0.05) production by cultured TAO cells only, an effect that was abrogated by inhibition of 11beta-HSD1. CONCLUSIONS: Induction of 11beta-HSD1 activity and expression by inflammatory cytokines (TNF-alpha, IL-6) may enhance orbital adipocyte differentiation (adipogenesis) and limit proliferation in TAO. 11beta-HSD1 may also have a role in regulating the local orbital inflammatory response.